2012
DOI: 10.7150/ijbs.3524
|View full text |Cite
|
Sign up to set email alerts
|

An Anti-PCSK9 Antibody Reduces LDL-Cholesterol On Top Of A Statin And Suppresses Hepatocyte SREBP-Regulated Genes

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a promising therapeutic target for treating coronary heart disease. We report a novel antibody 1B20 that binds to PCSK9 with sub-nanomolar affinity and antagonizes PCSK9 function in-vitro. In CETP/LDLR-hemi mice two successive doses of 1B20, administered 14 days apart at 3 or 10 mpk, induced dose dependent reductions in LDL-cholesterol (≥ 25% for 7-14 days) that correlated well with the extent of PCSK9 occupancy by the antibody. In addition, 1B20 induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 46 publications
8
79
1
1
Order By: Relevance
“…Moreover, treatment with the 1B20 antiPCSK9 monoclonal antibody in mice and rhesus monkeys led to robust LDL-cholesterol lowering in plasma decreased liver PCSK9 and LDL mRNAs, and transient increases in total plasma levels of PCSK9 [61].…”
Section: In the Proprotein Convertase Subtilisin Kexine Type 9 Genementioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, treatment with the 1B20 antiPCSK9 monoclonal antibody in mice and rhesus monkeys led to robust LDL-cholesterol lowering in plasma decreased liver PCSK9 and LDL mRNAs, and transient increases in total plasma levels of PCSK9 [61].…”
Section: In the Proprotein Convertase Subtilisin Kexine Type 9 Genementioning
confidence: 98%
“…A recent study showed that antibody 1B20, which binds to PCSK9 with high affinity, disrupts the PCSK9-LDL receptor interaction, and inhibits the effect of PCSK9 on cellular LDL uptake [61]. Moreover, treatment with the 1B20 antiPCSK9 monoclonal antibody in mice and rhesus monkeys led to robust LDL-cholesterol lowering in plasma decreased liver PCSK9 and LDL mRNAs, and transient increases in total plasma levels of PCSK9 [61].…”
Section: In the Proprotein Convertase Subtilisin Kexine Type 9 Genementioning
confidence: 99%
“…The LLOQ was selected close to the concentration of endogenous sPD-1 levels in normal human sera (~100 pg/mL). This assay was designed and proven to measure sPD-1 in the presence of nivolumab (see last section of Results), the levels of total sPD-1 post drug treatment may increase significantly since the clearance of analyte-antibody complex were expected to be slower based on our experience with other circulating proteins (18). Therefore, the ULOQ was selected at 10,000 pg/mL so that the calibration curve covers a wide range of concentrations.…”
Section: Standard Curve and Assay Rangementioning
confidence: 99%
“…This function of APLP2 PCSK9 remains intact and accumulates in the circulation, which reduces the duration of action of anti-PCSK9 mAbs (discussed below). Accumulation of circulating PCSK9 was observed in animal studies in multiple anti-PCSK9 mAbs ( 31,32 ), including an increase of >20-fold in monkeys. A signifi cant accumulation of total PCSK9 was also observed in humans treated with an anti-PCSK9 mAb ( 23 ).…”
Section: Proteolytic Cleavage Of Pcsk9 Slows the CL Of Ly From Serummentioning
confidence: 99%
“…The serum concentration of PCSK9, which included the antibody-bound and free forms of both intact and truncated PCSK9, was measured in the monkeys as an index of target engagement. Previous studies in anti-PCSK9 mAbs in mice, monkeys and humans have demonstrated as much as 20-fold accumulation of circulating PCSK9 ( 23,31,32 ), due to slower PCSK9 clearance (CL) when bound to a therapeutic antibody. However, serum PCSK9 concentration did not increase in monkeys treated with LY, similar to monkeys treated with a control IgG4 ( Fig.…”
Section: Binding and Effi Cacy Of Lymentioning
confidence: 99%